In Silico Analysis of CKIN/SnRK Genes for Osmotic Stress Responsive in Genomic Elements Pigeon Pea (Cajanus cajan L.) - Arti; Srivastava, Shobhit Kumar; Sharma, Manoj Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The SnRK2 (SNF1-related protein kinase 2) gene family is a critical regulator of abscisic acid (ABA) signaling pathways, orchestrating plant responses to abiotic stresses such as drought and salinity. In the pigeon pea (Cajanus cajan L.), a diploid legume adapted to semi-arid tropics, an extraordinary expansion of this gene family has been identified, with 1,210 putative genes. This study focuses on 245 CcSnRK2 genes possessing the Pkinase_Tyr domain, exploring their structural diversity, functional domains, subcellular localization, conserved motifs, physicochemical properties, and phylogenetic relationships. Homology-based identification using BLASTP and Conserved Domain Database (CDD) analysis confirmed the presence of the Pkinase_Tyr domain, suggesting potential dual-specificity kinase activity. Notably, 46 genes exhibit nuclear localization, indicating roles in transcriptional regulation of stress-responsive genes. Phylogenetic analysis, conducted using ClustalW and MEGA 6.0, grouped these genes into four clades, reflecting functional diversification likely driven by gene duplication and polyploidy. Physicochemical properties, analyzed via ProtParam, reveal diverse protein architectures suited for stress adaptation. These findings highlight the SnRK2 family’s pivotal role in pigeon pea’s resilience and provide a foundation for molecular breeding to enhance crop tolerance in challenging environments.